Hydroxyapatite-collagen- carboxylic carbon quantum dot composite loaded with chrysin supported the proliferation and differentiation of human bone marrow derived mesenchymal stem cells - Zhou, Ao; Chen, Sinan; Mickymaray, Suresh; Alqurashi, Yaser E.; Jeraud, Mathew; Chen, Biao; Hu, Yunjiu (Frontiers in Materials, 2022)
Developing a bioactive with biocompatible scaffold material is a substantial approach for bone regeneration and functional healing. Hydroxyapatite (HAP) is the main component in bone formation as an inorganic component and regeneration due to its osteoconductive properties. In this study, we prepared a scaffold material composed of HAP and collagen (COL) cross-linked via carboxylic carbon quantum dot (CCQD) with chrysin (CRN) molecule. CRN is a flavonoid that has been shown to encourage the bone development of bone marrow stem cells. It is loaded for enhancing bone regeneration and HAP's ability. XRD, FT-IR, SEM, and TEM analysis have characterized the prepared composites for their crystalline nature, functional behavior, and morphological evaluations. The HAP has retained its original crystalline lattice confirmed from XRD analysis in the prepared composites. The addition of CRN molecule has decreased the length of HAP rods from ~932 nm to ~459 nm, as confirmed by TEM images. The increased particle sizes have been observed for the prepared composites. It reaches the maximum at 938.0 nm for the final HAP/COL/CCQD/CRN composite, which was confirmed by particle size analysis. The in-vitro CRN release behavior shows that the CRN molecule has controlled release up to 23% for 48 hrs. The biocompatibility of prepared material was investigated and confirmed on human bone marrow-derived mesenchymal stem cells (hBMSCs). This examination has proven that the prepared material has a good ability for bone cell regeneration. The material may apply for bone regeneration applications after in-vivo and clinical investigations.